2022
DOI: 10.1007/s40766-022-00029-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable glasses: new perspectives for an old problem

Abstract: Ultrastable glasses (mostly prepared from the vapor phase under optimized deposition conditions) represent a unique class of materials with low enthalpies and high kinetic stabilities. These highly stable and dense glasses show unique physicochemical properties, such as high thermal stability, improved mechanical properties or anomalous transitions into the supercooled liquid, offering unprecedented opportunities to understand many aspects of the glassy state. Their improved properties with respect to liquid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 236 publications
(379 reference statements)
1
22
1
Order By: Relevance
“…The glass transition temperature ( T g ) was measured through spectroscopic ellipsometry, which has the advantage of determining T g from as-deposited films with a greater (>10 3 times) sensitivity, compared to conventional differential scanning calorimetry (DSC). Each film of ∼200 nm was deposited on silicon wafer substrates by a thermal coevaporation at a deposition rate of ∼2 Å s –1 and the substrate temperature during the deposition process was not controlled meaning that the deposition temperature of the films ranged from 0.80 T g to 0.89 T g , depending on the mixing ratio. Although there are reports of films with ultrastable properties, such as higher density compared to those of ordinary glass, may form at the similar deposition temperatures relative to T g , no evidence of ultrastable behavior was observed in the current study, judging from the thickness change after the first temperature cycle. The sample was heated and cooled at rates of 10 °C min –1 and 5 °C min –1 , respectively.…”
contrasting
confidence: 69%
“…The glass transition temperature ( T g ) was measured through spectroscopic ellipsometry, which has the advantage of determining T g from as-deposited films with a greater (>10 3 times) sensitivity, compared to conventional differential scanning calorimetry (DSC). Each film of ∼200 nm was deposited on silicon wafer substrates by a thermal coevaporation at a deposition rate of ∼2 Å s –1 and the substrate temperature during the deposition process was not controlled meaning that the deposition temperature of the films ranged from 0.80 T g to 0.89 T g , depending on the mixing ratio. Although there are reports of films with ultrastable properties, such as higher density compared to those of ordinary glass, may form at the similar deposition temperatures relative to T g , no evidence of ultrastable behavior was observed in the current study, judging from the thickness change after the first temperature cycle. The sample was heated and cooled at rates of 10 °C min –1 and 5 °C min –1 , respectively.…”
contrasting
confidence: 69%
“… 24 It is also important to mention that Zhang and Fakhraai have reported that the surface diffusion and relaxation dynamics are indeed decoupled. 25 A more detailed discussion on the factors affecting the ultrastability has recently been published by Rodríguez-Tinoco et al 26 …”
Section: Introductionmentioning
confidence: 99%
“…24 It is also important to mention that Zhang and Fakhraai have reported that the surface diffusion and relaxation dynamics are indeed decoupled. 25 A more detailed discussion on the factors affecting the ultrastability has recently been published by Rodri ́guez-Tinoco et al 26 Moving to the properties of vapor-deposited glasses, they are known to be substantially influenced by processing conditions. For instance, the rate of material deposition affects the structural anisotropy, thermal stability, and density of the vapor-deposited glass.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The agreement between our observed T g values and the value reported by Van den Brande et al clearly indicates the authenticity of the meltblending method. As pointed out in recent papers, 12,13 some studies have struggled to explain their results based on the 15 In this case, the disagreement with the reported bulk T g was explained since it would be induced by the interaction between the substrate and the CBP layer. 16 These reported phenomena can be explained easily and simply with the corrected T g value.…”
mentioning
confidence: 92%
“…The agreement between our observed T g values and the value reported by Van den Brande et al clearly indicates the authenticity of the melt-blending method. As pointed out in recent papers, 12,13 some studies have struggled to explain their results based on the correct T g value. Mu et al concluded that the smoothness of the CBP film surface at 69 °C was related to the T g of CBP , despite the dramatic change of the film morphology and device performance at 105 °C.…”
mentioning
confidence: 99%